Synthesis, characterization and properties of some rare earth complexes with 2,6-pyridine dicarboxylic acid and α-Picolinic acid - 黄进 徐莹豪 陈小轲 许东芳 徐燕鸣 何其庄 (Journal of rare earths, 2012)
Five novel ternary complexes were synthesized by the rare earth with 2,6-pyridine dicarboxylic acid and α-picolinic acid. These complexes were characterized by elemental analysis, molar conductivity, FT-IR, UV-Vis, Raman, TG-DTA and XRD. The general formula of the complexes was [RE（DPA）（L^α）（H2O）].2H2O （RE=Pr^3＋, Nd^3＋, Sm^3＋, Eu, Er^3＋; DPA=2,6-pyridine dicarboxylic acid; L^α=α-picolinic acid）. The investigation of fluorescence properties of the Eu-complex showed that the Eu（Ⅲ） ion could be sensitized efficiently by the ligand to some extent. The antibacterial activity test indicated that all the five complexes exhibited antibacterial ability against Escherichia coli and Staphylococcus aureus with broad antimicrobial spectrtmas.